[Buffalypso herd in the ponds] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Bisons in the ponds at La Gloria Estate.
Cataloger's title
Keywords: Livestock; Bison farming -- Trinidad and Tobago; Caroni (1975) Limited